Compliance with measures to repair and build peace culture in Ecuador and Chile - Reyes-Valenzuela, Carlos (2021)
The objective of this work is to identify how the impacts of the Truth Commissions Reports in Chile and Ecuador have promoted compliance with comprehensive reparation measures and their relationship with the construction of the Culture of Peace (CP). Two studies were carried out: the first one, whose objective was to design and validate the content, an instrument to measure the perception of a culture of peace. The second one seeks to evaluate the knowledge of integral reparation measures as an intervening variable between the attitudes towards the work of the Commissions and the state functions of the CP. The implications of the lack of compliance with comprehensive reparation measures and their relationship with the construction of CP in post-conflict societies are discussed.